SISTEM INFORMASI TRANSAKSI KEUANGAN UNIT TOKO PRIMKOPOL SEKRETARIAT UMUM MABES POLRI JAKARTA - Vina Oktaviyani; Sri Muryani; Syahbaniar Rofiah (LPPM STMIK ANTAR BANGSA, 2015)
Abstract– Unit stores Primkoppol General Secretary of Police Headquartes Jakarta is a form of business that is engaged in cooperative. Settlement of financial transactions on Unit Stores Primkoppol General Secretary of Police Headquartes Jakarta is still done manually using media papers ranging from recording purchases, cash sales, credit sales, payment accounts, the making of the journal, posting to the general ledger, balance sheet before adjustments, adjusting entries, work sheet, and the financial statements. To the authors tried to make a final task of the settlement of finacial transactions on Unit Stores Primkoppol General Secretary of Police Headquartes Jakarta. With me development of the IT world is so rapid and all angels have been touched by the activities of a computer, the process of management accounting is no longer a complicated issue that requires expertise to be someone who understands accounting. With the help of an accounting program, anyone will be able to carry out the task of accounting unit stores, despite having no background in accounting though. Zahir as a fairly reliable software in the field of accounting, finance unit store have the ability to manage easily and flexibly. And it will be reviewed and the authors pointed out in the discussion of this paper. Intisari—. Unit Toko Primkoppol Setum Polri Jakarta merupakan bentuk usaha yang bergerak di bidang perkoperasian. Penyelesaian transaksi keuangan pada Unit Toko Primkoppol Setum Polri Jakarta masih dilakukan secara manual menggunakan media kertas mulai dari pencatatan pembelian, penjualan tunai, penjualan kredit, pembayaran piutang, pembuatan jurnal, posting ke buku besar, laporan neraca sebelum penyesuaian, jurnal penyesuaian, neraca lajur dan laporan keuangan. Untuk itu penulis mencoba membuat penelitian mengenai penyelesaian transaksi keuangan pada Unit Toko Primkoppol Sekretariat Umum Mabes Polri Jakarta. Dengan perkembangan dunia IT yang sedemikian pesat dan semua sudut aktifitas telah tersentuh oleh komputer, maka proses pengelolaan akuntansi bukan lagi persoalan rumit yang membutuhkan keahlian seorang yang harus mengerti akuntansi. Dengan bantuan program akuntansi, siapa saja akan mampu mengemban tugas keuangan unit toko, eskipun tidak memiliki latar belakang akuntansi sekalipun. Zahir sebagai perangkat lunak yang cukup handal dibidang akuntansi, memiliki kemampuan mengelola keuangan unit toko dengan mudah dan fleksibel. Dan hal tersebut yang akan penulis kaji dan kemukakan dalam pembahasan tulisan ini. Kata kunci : Sistem Informasi, Transaksi Keuangan, Unit Toko Primkopol, Mabes Polri Jakarta